(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
The purpose of this study was to compare the renal function in patients undergoing coronary artery bypass grafting in off-pump and on-pump having pre-operative impaired renal function. In the on-pump, the serum creatinine and urea levels were significantly increased on post-operative day 1, 3 and 7. On day 1, it was maximum, then gradually decreased but not reached to pre-operative level. In case of off-pump, serum creatinine and urea levels were significantly increased on post-operative day 1 and 3. On day 1, it was maximum. Then decreased and the serum creatinine reached below pre-operative level on day 7. In case of on-pump, the creatinine clearance rate was significantly decreased on post-operative day 1, 3 and 7. On day 1, it was minimum. Then gradually increased but not reached the pre-operative level. In case off-pump, the creatinine clearance rate was significantly decreased on day 1 and 3. On day 1, it was minimum, then gradually increased and reached above the pre-operative level. A significant low level creatinine clearance rate was observed in on-pump group. Renal function was better preserved in patients undergoing off-pump in comparison to on-pump coronary artery bypass grafting.